Helyi gazdaságfejlesztés Bazsi községben - Kápolnai, Zsombor; Takács, Kristóf; Takács, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
In the last few years, an impressive economical progress has been noticeable in Bazsi, this little village in Veszprém county: for example, the incomings of the local government has been increasing etc. These results can be explained as the effects of the local economic development that the local government started about ten years ago. This development is based mostly on the agricultural traditions of the settlement: by the local system of public works, the local government is growing native apple species and cucumber, and this system seems to become sustainable in medium-term. In this study, we analyze the background of this progress; to reach this object, we have made interviews with the people who are important in the local economy and we have analyzed the significance data that are available in this subject.